Featured Cover. (15th August 2022) - Zhao, Zhiming; Koulouzis, Spiros; Bianchi, Riccardo; Farshidi, Siamak; Shi, Zeshun; Xin, Ruyue; Wang, Yuandou; Li, Na; Shi, Yifang; Timmermans, Joris; Kissling, W. Daniel
Abstract : The cover image is based on the Research Article Notebook‐as‐a‐VRE (NaaVRE): From private notebooks to a collaborative cloud virtual research environment by Zhiming Zhao et al., https://doi.org/10.1002/spe.3098 .